The Influence Of Promotion, Perceived Ease Of Use, And Price Toward Repurchase Intention Transportation Services Go-Jek Indonesia - Farida Islamiah; Dedy Darmawan; Sri Asmirani (Economics and Digital Business Review, 2025)
This study investigates the influence of promotion, perceived ease of use, and price on repurchase intention in the context of Go-Jek’s transportation services. The rapid growth of ride-hailing platforms has heightened competition, compelling companies to adopt strategies that ensure customer retention. This research employs a quantitative approach, utilizing surveys distributed to a sample of Go-Jek users. The findings reveal that promotion significantly enhances customer repurchase intention by creating perceived value and fostering loyalty. Perceived ease of use also plays a crucial role, as users prioritize platforms that are user-friendly and efficient. Additionally, price sensitivity remains a key determinant, with competitive pricing strategies strengthening repurchase behavior. These results underline the need for Go-Jek to continuously innovate in promotional activities, maintain a seamless user experience, and offer affordable pricing to secure long-term customer relationships. The study contributes to a deeper understanding of consumer behavior in the digital ride-hailing industry and provides actionable insights for managerial practices.